Associations between renal tubular lesions and clinical parameters as well as prognosis in diabetic kidney disease - Shao Xiao-lin; Luo Yu-qing; Ma Dong-hong; Deng Xi-wen; Guo Ming-hao (Linchuang shenzangbing zazhi)
ObjectiveTo explore the associations between renal tubular lesions under light microscope and clinical parameters in diabetic kidney disease （DKD） and provide clinicopathological evidence for adverse progression of DKD patients.MethodsFrom January 2018 to April 2021， a total of 126 DKD patients diagnosed by renal biopsy were recruited. Follow-ups ended in September 2021. Progression of renal dysfunction （renal replacement therapy or doubling of serum creatinine） was employed as an outcome parameter. According to microscopic degree of renal tubular lesions， there were light tubulopathy （LT， n=41）， moderate tubulopathy （MT， n=40） and severe tubulopathy （ST， n=45）.ResultsCompared with MT and ST groups， serum creatinine， blood urea nitrogen， cystatin C （Cys C）， total cholesterol， low-density lipoprotein， α1-microglobulin （α1-MG）， β2-microglobulin （β2-MG）， retinol binding protein （RBP）， urinary albumin/creatinine ratio， high sensitivity C-reactive protein （hs-CRP）， neutrophil/ lymphocyte ratio （NLR）， monocyte/ lymphocyte ratio （MLR）， glomerulosclerosis ratio， pathological classification and clinical stage were lower in LT group. And eGFR， blood calcium and blood albumin was higher in LT group （P<0.05）. Spearman’s correlation analysis revealed that renal tubular lesions with NLR （r=0.205， P=0.021）， MLR （r=0.196， P=0.028）， hs-CRP （r=0.203， P=0.023） with α1-MG （r=0.280， P=0.001）， β2-MG （r=0.348， P<0.001）， RBP （r=0.495， P<0.001）， with serum creatinine （r=0.627， P<0.001）， blood urea nitrogen （BUN）（r=0.587， P<0.001）， Cys C （r=0.727， P<0.001）， glomerulosclerotic ratio （r=0.416， P<0.001）， pathological classification （r=0.628， P<0.001） and clinical stage （r=0.578， P<0.001） were positively correlated. Univariate Cox regression analysis showed MT， ST， serum creatinine， blood urea nitrogen， Cys C， NLR and platelet/lymphocyte ratio （PLR） were the risk factors of adverse progression. Serum albumin， blood calcium and estimated glomerular filtration rate （eGFR） were the protective factors. Multivariate Cox regression analysis indicated that both MT and ST were independent risk factors for progression of renal dysfunction in models 1， 2 and 3. Kaplan-Meier survival curve showed that degree of renal tubular lesions was significantly correlated with progression of renal dysfunction （P<0.001）. ROC curve indicated that AUCs of NLR， MLR， PLR， α1-MG， β2-MG， RBP， Cys C， serum creatinine and BUN for renal dysfunction were 0.638， 0.635， 0.553， 0.678， 0.732， 0.770， 0.853， 0.804， 0.793， sensitivities 38.8%， 42.5%， 81.3%， 67.5%， 81.3%， 72.5%， 77.5%， 72.5% and 62.5%； specificities 85.0%， 82.5%， 32.5%， 65.0%， 67.5%， 75.0%， 85.0%， 80.0% and 87.5%； cut-off values 3.60， 0.22， 105.37， 39.34 mg/L， 0.69 mg/L， 2.74 mg/L， 1.42 mg/L， 77.90 umol/L and 7.80 mmol/L.ConclusionTubulopathy is an independent risk factor for progression of renal dysfunction. NLR， MLR， α1-MG， β2-MG， RBP， Cys C， serum creatinine and BUN have certain clinical values in predicting progression of renal dysfunction.